Response of Ethiopian field pea (Pisum sativum L.) cultivars to phosophorus fertilization of Nitosols - Amanu, Amare Ghisaw (University of the Free State, 2003)
Field pea (Pisum sativum L.) is the third most important grain legume in Ethiopia where its productivity is constrained by several biotic, abiotic and socioeconomic factors. The crop is grown mainly on a wide range of soil types throughout the highlands (1800 to 3200 m.a.s.l.) in well drained soils like Nitosols that developed from volcanic rocks. Nowadays the blanket recommendation of diammonium phosphate (DAP) at 100 kg ha" to this low input crop is questioned by the farmers and development workers. Hence, experiments have been conducted with the major objective of quantifying the response of Ethiopian field pea cultivars to phosphorus fertilization of Nito soIs under both glasshouse and field conditions. Glasshouse experiments: Topsoil from Ilala and Cheffa were used. Experiments were laid out in a split plot design with three phosphorus fertility levels (Extractable phosphorus: low = 5, medium = 15 and high = 30 mg kg-I) as the main plot treatments and factorial combinations of two pea cultivars (TIala soils: Holetta and G22763-2C; and Cheffa soils: Tegegnech and Cheffa local) and six phosphorus application rates (0, 7.5, 15, 30, 60 and 120 mg P kg") as the sub-plot treatments in a randomized complete block design with four replications. The phosphorus fertility levels together with the phosphorus application rates had positive influences on the growth and development of the pea crop as manifested in the biomass yield of the different cultivars. Critical phosphorus levels were estabilished by relating relative biomass yield to extractable soil phosphorus. In the case of the Bray 2 extractions, the critical phosphorus levels for TIala soils were 14 and 15 mg P kg" for cvs. G22763-2C and Holetta respectively, for Cheffa soils 17 and 20 mg P kg" for cvs. Cheffa local and Tegegnech respectively. However, in the case of Olsen extractions the critical phosphorus levels for TIala soils were 17 and 27 mg P kg" for cvs. Holetta and G22763-2C respectively, and for Cheffa soils 20 and 22 mg P kg" for cvs. Cheffa local and Tegegnech respectively Field experiments: Two sets of experiments were conducted, viz. the first set at Holetta (1996 to 1999) and Bekoji (1996 to 1998) and the second set in 2001 at TIalaand Cheffa. For the first set of experiments a factorial combination of five phosphorus rates (0, 10, 20, 40 and 60 kg P ha") and three pea cultivars (Holetta site: Tegegnech, G22763-2C, Holetta local; and Bekoji site Tegegnech, G22763-2C and Cheffa local) were laid out in a randomized complete block design with four replications. On the other hand, for the second set of trials a split plot design was used with three phosphorus fertility levels (Extractable phosphorus: low = 5, medium = 15 and high = 30 mg kg") as the main plot treatments and the factorial combinations of five phosphorus application rates (0, 10, 20, 40 and 80 kg ha") and two pea cultivars (llala site: G22763-2C and Holetta; and Cheffa site: Tegegnech and Cheffa local) as the sub-plot treatments which were replicated four times. At the Holetta and llala sites, grain yield response of the pea crop to phosphorus a.pplication was poor regardless of the phosphorus application rates or the cultivars . As a result, low marginal rate of returns (MRRs) were computed which implicated that phosphorus fertilization is not economically viable. On the contrary, at the Bekoji and Cheffa sites, the grain yield response of the pea crop to the application of phosphorus was good with significant differences between phosphorus fertility levels and cultivars. The interaction of phosphorus application rate and cultivars was significant (p < 0.05). A MRR of 100% was obtained at an application of21 kg P ha-I for cv. Tegegnech, 10 kg P ha" for cv. G22763-2C and 5 kg P ha-I for cv. Cheffa local. The 100% MRR computed implicated that phosphorus fertilization to all cultivars at the low phosphorus fertility level was economically viable with the current prices of grain and fertilizer in the zone. Unfortunately, no critical soil phosphorus levels could be estabilished under field conditions. The critical soil phosphorus levels that were established under glasshouse conditions should therefore still be validated in the field. However, the fact that the pea crop did respond to phosphorus application mainly at the low phosphorus fertility levels in the field confirms already to some extent their validity. In general, the improved pea cultivars responded better to phosphorus fertilization than the local cultivar. A thorough investigation on phosphorus use efficiency of pea genotypes to' identify low phosphorus requiring ones should be considered to benefit resource poor farmers. The aspect of soil pH modifications through liming, and the use of non-nitrogenous phosphorus fertilizer sources for field peas are recommended.
Thesis (Ph.D. (Soil, Crop and Climate Sciences))--University of the Free State, 2003
Keywords: Phosphorus in agriculture -- Ethiopia; Phosphatic fertilizers -- Ethiopia; Peas -- Fertilizers -- Ethiopia